KEPATUHAN MINUM OBAT PADA PENDERITA DM TIPE II - Deomedes; Rahmawati, Annisa; Pradika, Jaka (Jurnal Riset Keperawatan dan Kesehatan, 2025)
Background: Diabetes Mellitus (DM) is a chronic disease that requires long-term management, including medication  adherence,  to  prevent  complications.  However,  medication  adherence  among  DM  patients  remains  low  in  various  regions. Objective: To describe the level of medication adherence among patients with Type II Diabetes Mellitus in the working  area of Manis Mata Health Center, Ketapang. Methods: This descriptive study used a total sampling technique involving 70 respondents diagnosed with Type II DM. Data were collected using the Morisky Medication Adherence Scale (MMAS-8) questionnaire and analyzed univariately to obtain the frequency distribution of respondent characteristics and adherence levels. Results: Most  respondents  were  aged  56–66  years  (45.7%),  female  (58.6%),  had  a  junior  high  school  education (40.0%), were unemployed (37.1%), and had suffered from DM for more than 5 years (70.0%). The level of medication adherence was very low, with 94.3% of respondents being non-adherent, 5.7% moderately adherent, and 0% fully adherent. Advanced age, low education, unemployment, and longer duration of illness were the main contributing factors to poor adherence. Conclusion: Medication adherence among patients with Type II DM in this study area was very low. Comprehensive interventions,  continuous  health  education,  family  support,  and  optimization  of  non communicable  disease  control programs at the primary care level are essential to improve patient adherence.